A map of the Champagne region of France. Engraving by J. le - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: A map of the Champagne region of France. Engraving by J. le. A map of the Champagne region of France. Engraving by J. le Clerc, 1616, after D. de Templeux, 1616. Iconographic Collections Keywords: Sieur de Frestoy | Jean Leclerc | Damien de Templeux
Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons